Forecast of the Dynamics of the Number of Russian Banks Until 2025 - D. S. Rukavishnikov (Управленческое консультирование, 2018)
Effective functioning of the banking system is a prerequisite for the development of market relations in Russia, which objectively determines the key role of the Central Bank in regulating banking activities. Banks form an integral part of the modern money economy. Their activities are closely related to the needs of production. Being in the center of economic life, serving the interests of producers, banks mediate the links between industry and commerce, agriculture and the population. Banks are an attribute not of an individual economic region or of any one country. Their sphere of activity has neither geographical nor national borders, this phenomenon, which has tremendous financial power, considerable monetary capital.In recent years, the Russian banking system has experienced a period of purification. The number of financial and credit organizations in Russia is declining every year, and it is not just about small banks, but also about large banking institutions. A difficult period in the work of Russian banks is connected not only with the difficult economic and foreign policy situation in Russia. The regulator, represented by the Central Bank of the Russian Federation (hereinafter referred to as the Central Bank of the Russian Federation), pursues a strict policy of consolidating the banking sector through various mechanisms: revocation of the license, rehabilitation of troubled banks, through the «Banking Sector Consolidation Fund». In view of the constant reduction and consolidation of Russian financial and credit organizations, the issue of studying the dynamics of the number of the Russian banking system is becoming topical.The purpose of the study is to determine the dynamics of the development of the Russian banking sector, and also to build a forecast of the number of financial and credit organizations until 2025.In the course of the research, general scientific methods of management theory, expert, statistical and comparative analysis were applied.The article analyzes the number of Russian financial and credit institutions and regional binding, as well as the methods of reorganization used. The current dynamics of the development of the banking sector, its tendency to consolidation, the forecast of the number of Russian banks is revealed.